Formação de professores centrada na escola : uma reflexão sobre a experiência nas escolas de educação infantil da rede pública municipal de Primavera do Leste - Silva, Paulo Sérgio da (2018)
Understanding the context in which school-centered training takes place may be the primary step in establishing a coherent dialogue, focusing on the real needs of each school with its specific problems. In this sense, this work presents an understanding of ongoing formation based on authors such as Freire, Imbernón, Nóvoa, Pacheco, among others, with emphasis in the school space because it understands that it is through the reflection of the teaching practice that the development is achieved forming teachers' identity and autonomy. The main objective of this work is to understand the development of permanent education centered on the school and its importance for the teachers from their experiences in the study groups and in the spaces of public schools of the municipal network of pre - primary education in. This understanding is based on the conception of Freire's problematic and liberating education (2016) that permeates the understanding that we are unfinished beings, unfinished, therefore, in constant need of search for knowledge. Promoting change in education requires rather a committed stance, based on the universal values of the human being and engaged in the construction of a project of society that conceives the human person as protagonist of its development and that promotes the autonomy of the teacher. This research was developed in a qualitative approach, since its object of investigation is the process of continuing education centered in the school and the subjects researched are the teachers who participated in this process as guiding the formation, but that in guiding their peers, also develop in the exchanges of knowledge, both theoretical, as well as the knowledge of experiences made. The results of this research were illuminated by the dialectical method in the Freirean perspective that allows us to walk safely toward a deeper understanding of the social reality of this research. The analysis of the school projects showed an evolution during the two years in which the research was extended, especially regarding the importance of understanding the theoretical conceptions as a condition to understand the educational practice. The answers presented by the interviewed teachers raised some notes that elevate school-centered training as essential to the development of the teaching profession, since it contributes to the quality of teaching.